Institusional role in analysis of installation of Tsunami Natural Disaster Detection Equipment using Analytical Hierarchy Process (AHP) and Cost Benefit Analysis Methods - Manurung, Yanto. S; Widjayanto, Joni; Saragih, Herlina (Technium Social Sciences Journal, 2022)
The problem of natural disasters, such as tsunamis, tends to increase from year to year, mainly due to Indonesia's location in the Pacific Ring of Fire (Ring of Fire) and exacerbated by the lack of tools that can inform early for people if a geological disaster will occur and the lack of early warning for geological disasters installed according to local needs. The tsunami disaster will have a harmful and destructive impact on an area where the community suffers a significant material loss. Therefore, this study aims to determine the priority weight of each region in installing early warning tools to minimize the risk of geological disasters in Indonesia using the AHP (Analytical Hierarchy Process) and Cost-Benefit Analysis methods. This type of research is descriptive exploratory research, using qualitative data analysis methods—classifying regional criteria in Indonesia to determine the installation zone for early detection of natural disasters. The weighting and assessment are carried out on regional factors. Early detection tools for natural disasters are determined using the Analytical Hierarchy Process (AHP) method, which provides subjective calculations based on the hierarchical structure of regional components, namely Dense Settlements, Business Activities, Strategic Buildings Conservation Areas. The subjective calculation is combined with sub-criteria components from the area in coastal settlements, urban settlements, significant business activities, small business activities, important strategic buildings, historical strategic buildings, water conservation areas, and wildlife conservation areas. They support data taken directly through questionnaires and secondary data as comparison data. The data and results of AHP calculations are presented in the form of a parameter table based on the factor component of the regional component. The results of the analysis show that the detectors are divided into four types, namely CBT, Buy, Gauge, and ISDL